Power and security in Northeast Asia shifting strategies - Kim, Byung-Kook; Jones, Anthony, 1940- (Lynne Rienner Publishers, 2007)
As China's influence rises and the US attempts to retain its primacy in Northeast Asia, the countries of the region are reconsidering their own security needs - and availing themselves of new opportunities. This book explores the complexities of current security strategies in the region.